2014
DOI: 10.1161/circimaging.114.002397
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Left Ventricular Interstitial Fibrosis in Asymptomatic Chronic Primary Degenerative Mitral Regurgitation

Abstract: Background-The optimum timing of surgery in asymptomatic patients with chronic severe primary degenerative mitral regurgitation (MR) remains controversial, and further markers are needed to improve decision-making. There are limited data that wall stress is increased in MR and may result in ventricular fibrosis. We investigated the hypothesis that chronic volume overload in MR is a stimulus for myocardial fibrosis using T1-mapping cardiac MRI. Methods and Results-A cross-sectional study of 35 patients (age 60±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 37 publications
4
79
3
1
Order By: Relevance
“…Although the study of Han et al 13 did not show LGE elsewhere in the myocardium, the study of Van De Heyning et al 14 of 39 patients with primary MR (all but 4 of whom had degenerative MR) noted that 12 patients (31%) had LGE; 3 with an infarct pattern, 7 with a nonischemic pattern, and 2 patients with a combined pattern. These are similar to the LGE results of the study of Edwards et al 5 although the latter reports a higher number of subjects with a diffuse fibrosis pattern. These differences are most likely attributable to the small sample size in both studies.…”
Section: Previous Studiessupporting
confidence: 90%
See 3 more Smart Citations
“…Although the study of Han et al 13 did not show LGE elsewhere in the myocardium, the study of Van De Heyning et al 14 of 39 patients with primary MR (all but 4 of whom had degenerative MR) noted that 12 patients (31%) had LGE; 3 with an infarct pattern, 7 with a nonischemic pattern, and 2 patients with a combined pattern. These are similar to the LGE results of the study of Edwards et al 5 although the latter reports a higher number of subjects with a diffuse fibrosis pattern. These differences are most likely attributable to the small sample size in both studies.…”
Section: Previous Studiessupporting
confidence: 90%
“…In their study, Edwards et al 5 report that LGE distributed in a noncoronary pattern was present in 11 of 35 (31%) patients with MR versus none of the controls and that both mean ECV and native T1 times were greater in MR patients than in normal controls. Using 0.297 (29.7%) as the upper limit of normal for ECV based on values for their control group, they noted that all patients with LGE and an additional 3 patients had increased ECV, suggesting that ECV might be a more sensitive test for fibrosis in these patients.…”
Section: Mri Methods For Detecting Fibrosismentioning
confidence: 92%
See 2 more Smart Citations
“…ECV was associated with increased LV end-systolic volume index (r=0.62, p<0.01), left atrial volume index (r=0.41, p<0.05), lower LV EF (r=-0.60, p< 0.01), longitudinal function (mitral annular plane systolic excursion, r=-0.46, p<0.01) and peak VO2 max (r=-0.51, p<0.05). A multivariate regression model showed LV end-systolic volume index and left atrial volume index were independent predictors of ECV (r 2 =0.42, p<0.01) [58,62]. A recent study by Bui et al [63] reported that patients with mitral valve prolapse with complex ventricular arrhythmia (ComVA) had significantly shorter post-T1 times when compared with patients with mitral valve prolapse without ComVA [324 (IQR 296-348) vs. 354 (IQR 327-376) ms; p=0.03] and only 5/14 (36%) had evidence of papillary muscle LGE.…”
Section: Mitral Regurgitation and Aortic Regurgitationmentioning
confidence: 99%